Pengaruh Hujan Terhadap Stabilitas Lereng Simpang Sugih Waras - Batas Kota Baturaja - Sary, Putri Indah; Gofar, Nurly (Jurnal Tekno, 2023)
This paper presents results of saturated and unsaturated stability analysis of slope failures along jalan Simpang Sugih Waras – Batas Kota Baturaja. Most slopes failures occurred after a heavy rainfall; thus, rainfall infiltration is identified as the cause of the failures. Four locations were selected for this study. Soil samples were collected and tested in laboratory. The results indicate that the slope was made of clay with low plasticity. In the absence of the exact time of failure, IDF curve was used to identify the critical rainfall. In this case 19mm/hr rainfall for 6 hr was selected from 10-year-return-period IDF curve developed based on 20 year of rainfall data from nearby rainfall station. Seep analyses were carried out on the four slopes to obtain the seepage induced by rainfall infiltration and change of pore water pressure. Slope stability analyses were performed at selected times during and after rainfall application. The results of slope stability analysis show that the critical condition for slope was at the end of rainfall. Among the four slopes analyzed in his study, slope height has the most influence on the slope stability.